Electrochemical Aging and Characterization of Graphite-Polymer Based Composite Bipolar Plates for Vanadium Redox Flow Batteries. Issue 8 (1st August 2022) - Gupta, Gaurav; Satola, Barbara; Komsiyska, Lidiya; Harms, Corinna; Hickmann, Thorsten; Dyck, Alexander
Abstract : Three bipolar plates (BPP) comprised of a composite of polypropylene or polyvinylidene fluoride polymer and varying average graphite particle size were studied for application in a vanadium redox flow battery (VRFB). The BPPs were electrochemically aged via 3000 cyclic voltammetry curves in 1.8 M VOSO4 + 2.0 M H2 SO4 electrolyte. After every 500th cycle the aging progression was determined by performing cyclic voltammetry on the bipolar plates in 0.1 M H2 SO4 solution where the double layer capacitance, the quinone/hydroquinone and the vanadium species redox activity were quantitatively evaluated. Prior to the aging, the composite plates were extensively characterized using various physical methods. The performed studies reveal that the wettability, surface roughness and accessible porosity of the bipolar plates significantly influence their electrochemical stability. Cycling tests in vanadium redox flow single cells at a constant current density of 60 mA cm −2 revealed a close correlation of the cell efficiencies to the electrochemical stability of the bipolar plates. Thus, the proposed electrochemical characterization method can be an effective foresight to predict the applicability of a bipolar plate in a vanadium redox flow battery.